Self-care needs in healthcare contexts: how to gather, read and fulfill them - Lucia Zannini (University of Bologna, 2014)
In light of a continuing education intervention (entitled "On the other side") conducted with a multi-professional group at a Northern Italian hospital, this paper offers a reflection on educational needs analysis for healthcare professionals. This process has been extensively investigated, including in the context of healthcare training, leading to the call for a multi-method approach to developing professionals' competencies in the interest of optimizing their patients' health and quality of life. However, when professionals' deepest inner need is for self-care to help them cope with the perceived heavy demands of clinical practice, educators may usefully adopt the phenomenological approach, which involves bracketing, the ability to see, taking responsibility and attending to professionals' emotional experience. The analysis of professionals' self-care needs should be viewed as a continuous process, to be implemented on an ongoing basis throughout the entire educational intervention, and as a practice that itself requires a caring attitude.